Augmentative and alternative communication for children with cerebral palsy. Issue 9 (September 2016) - Clarke, Michael; Price, Katie; Griffiths, Tom
Abstract: Children with cerebral palsy (CP) can experience a range of significant speech, language and communication difficulties. Those children with little or no intelligible speech can benefit from the provision of augmentative and alternative communication (AAC) systems. AAC approaches include training in the use of manual signs and/or symbol systems, as part of a 'total communication' approach, whereby all possible communicative modalities are considered as potentially useful. For children with severe motor impairment where the potential for signing is limited, intervention typically focuses on supporting symbol use through the provision of high-tech and low-tech communication systems. This review describes the categories of AAC systems available to children with CP, and outlines AAC assessment and intervention principles, drawing on the World Health Organisation's International Classification of Function, Disability and Health (ICF-CY). Given the complex health, motor, sensory, learning and communication needs of children with CP, AAC related assessment and intervention requires a multi-disciplinary perspective.